Pathogenicity of Three Species of «Phaeoacremonium» spp. on Grapevine in California - Whiting, Cameron; Adalat, Khan; Rooney, Suzanne; Gubler, W.D. (Phytopathologia Mediterranea, 2000)
Autoclaved sand was inoculated with Phaeoacremonium inflatipes, P. aleophilum and P. chlamydosporum.Single bud cuttings of grapes of cv. Chardonnay were placed in inoculated sand and incubated for three weeks at27°C. P. inflatipes was isolated from 66%, P. aleophilum from 59% and P. chlamydosporum from 7% of culturedcuttings. The effect of infection on callusing was also observed. Inoculation with P. chlamydosporum, P. aleophilumand P. inflatipes inhibited callus formation in 22, 62, and 72% of total cuttings respectively. Infection of the cuttingsby P. inflatipes, P. aleophilum and P. chlamydosporum significantly (P=0.0001) reduced number of roots, plant height,number of internodes, root elongation and dry weight of the above-ground parts. However no significant (P=0.1969)effect was found on root dry weight. Infection and vascular discoloration was found in spurs of the ‘Pinot Noir’ and‘Chardonnay’ inoculated with P. chlamydosporum, P. inflatipes and P. aleophilum inoculated through pruning wounds.Significant differences were found in extent of invasion in ‘Pinot Noir’ and ‘Chardonnay’ in response to inoculation.Invasion of spurs of ‘Pinot Noir’ and ‘Chardonnay’ inoculated with P. chlamydosporum was significantly more extensivethan invasion by P. inflatipes and P. aleophilum respectively (P=0.0001).